2004
DOI: 10.1103/physreve.70.046217
|View full text |Cite
|
Sign up to set email alerts
|

Detecting dynamical changes in time series using the permutation entropy

Abstract: Timely detection of unusual and/or unexpected events in natural and man-made systems has deep scientific and practical relevance. We show that the recently proposed conceptually simple and easily calculated measure of permutation entropy can be effectively used to detect qualitative and quantitative dynamical changes. We illustrate our results on two model systems as well as on clinically characterized brain wave data from epileptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
321
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 471 publications
(325 citation statements)
references
References 37 publications
3
321
0
1
Order By: Relevance
“…. ; m!Þ to denote the probability distribution of permutation p j , the PE for this scalar series was defined as (Cao et al 2004;Li et al 2010;Yi et al 2014)…”
Section: Pe and Oimentioning
confidence: 99%
See 2 more Smart Citations
“…. ; m!Þ to denote the probability distribution of permutation p j , the PE for this scalar series was defined as (Cao et al 2004;Li et al 2010;Yi et al 2014)…”
Section: Pe and Oimentioning
confidence: 99%
“…Earlier studies have shown that this kind of complexity measures is particularly suitable for non-stationary time series (Cao et al 2004;Keller et al 2014). They have been successfully applied to analyze epileptic and anesthetic EEG data (Ouyang et al 2010;Cao et al 2004;Keller et al 2014;Li et al 2007Li et al , 2008Li et al , 2010. In our previous study (Yi et al 2014), we have also used them to detect the complexity changes of EEG activity associated with manual acupuncture at acupoint ST 36 in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the accurate detection of transitions from a normal to an abnormal state, either due to hardware or software failure, or due to an attack, may improve diagnosis and treatment. The multi-scale decomposition given by the SSA approach, could be combined with the conceptually simple and computationally very fast concept of permutation entropy [26] to detect dynamical changes in the subset of noisy eigenloads, which are responsible for the transient behavior of the traffic load series. Besides, to encourage further experimentation, we have made our datasets available to the research community [31].…”
Section: Discussionmentioning
confidence: 99%
“…Complexity measures have been shown to be powerful tools for detecting dynamical changes in time series from epileptic patients [27] and in speech signals [20,28], for distinguishing chaotic signals from stochastic ones, for distinguishing among different degrees of stochasticity [29], for quantifying stochastic and coherence resonances [30], and for classifying spatio-temporal patterns [31,32] and neural networks [33,34] etc.…”
Section: Introductionmentioning
confidence: 99%